A Brief Report of Immunohistochemical Markers to Identify Aggressive Hepatoblastoma. Issue 9 (October 2018) - Singh, Vivekanand; Manalang, Michelle; Singh, Meenal; Apte, Udayan
Abstract : Hepatoblastoma (HB) is the most common malignant liver tumor in children. Although survival of patients has improved significantly over the last 2 decades, a significant number of patients do not respond to standard chemotherapy. We conducted a pilot study to understand if there was immunophenotypic difference between tumors that respond well to chemotherapy versus that do not. We selected 10 cases of HB from children presenting at our hospital. All patients had initial tissue diagnosis, underwent chemotherapy followed by surgical resection. The cases were divided into 2 groups: aggressive group with 5 cases (all of which had a poor response to chemotherapy); and a good clinical outcome group with 5 cases (all of which responded well to chemotherapy). We excluded the small cell variant of HB from the study because its poor clinical outcome is well known. To be placed in the aggressive group we used the following criteria: <70% necrosis following chemotherapy or recurrence/distant metastasis following chemotherapy. From tissue obtained before chemotherapy, 1 representative block of formalin-fixed, paraffin-embedded tissue was selected for immunohistochemistry. Following review of published literature, antibodies were selected to detect Survivin, PLK-1, Cytokeratin19 (CK19), N-Myc, Yap, Notch2, Hes1, Hes5, and C-Myc. Our results show that Survivin, CK19, and Yap have a diffuse (>75%) positive staining of tumor cells in the aggressive tumors compared with good outcome tumors. However, staining for Yap was weak. Interestingly, there was loss of nuclear expression of C-Myc in majority of tumor cells in aggressive tumors, whereas nuclear staining was retained in most tumor cells of good responders. The N-Myc and PLK-1 immunostains did not reveal any significant differences in the 2 groups of HB. The immunostains for Notch2, Hes1, and Hes5 showed weak to moderately strong staining in tumor cells, but there was no obvious difference in the 2 groups. Our pilot study suggests that in nonsmall cell HB, diffusely increased expression of Survivin and CK19, and loss of nuclear expression of C-Myc marks the tumors as having an aggressive course.